Criticism of astrology in the first centuries of Christianity (Circe de clásicos y modernos, 2024)
From the origins of the Christian message, astrology was seen as a threat because of the belief in astral fatalism, which threatened not only human freedom but also faith in divine Providence. However, the rejection of the influence of the stars had different nuances both among the Fathers of the Church and in the Gnostic schools. The arguments used against astrology came, in some cases, from pre-Christian Hellenic philosophy and found their main support in the rejection of cosmic determinism. Christianity added its reticence to the divinatory practices of astrologers. The Gospel episode of the star of the East was the most studied for the elaboration of the oldest Christian diatribes against astrology, among which the Valentinians who are behind the text of the Extracts of Theodotus, reviewed by Clement of Alexandria.
Keywords: destiny; providence; astral fatalism; Fathers of the Church; Gnostics